Benchmark portfolio selection and efficient diversification of Congolese Bank - Kapiamba , Joël N.; Mubenga , Pascal K.; Ulungu E.-L , Berthold; Mukendi , Patrick K. (International Journal of Applied Mathematical Research, 2024)
The study, based on available data on the Congolese banking sector has succeeded in establishing a benchmark of the ideal distribution of a bank’s credit portfolio by sector in order to improve its profitability while reducing the risk of default. This benchmark has been established on an exclusively quantitative basis on the results of three distinct methods of multi-criteria decision aid: AHP and TOPSIS. It can help banks to assess of the quality of their credit portfolio (or, at least, their sectorial allocation) relative to the latter, which is derived from the aggregates of the entire banking sector. It would benefit from being usefully combined with a more qualitative analysis that escapes the spectrum of this study taking into account the quality and availability of the guarantee, track record, etc. The Student t-test, as the correlation coefficient has shown that the results of our different methods are in perfect correlation with the data of the bank, and the difference of the discrepancies between our methods and the data of the bank are random, that is to say not significant.